Improve Consumer Purchasing Decisions Through Quality of Service, Promotion And Quality of Information At PT. Ng Tech Supplies - Septa Diana Nabella (Publisher Cv. Inara, 2021)
The main objective of this research is to analyze the influence of service quality, promotion and information quality on customer purchasing decisions at PT. Ng Tech Supplies. This research is causal research (cause-effect research) . The population and sample in this study were 164 regular customers during January 2019 to July 2019 period. The sampling technique that the researcher used in this study was the simple random sampling technique. So that the sample in this study was 116 respondents. The results showed that partially service quality and information quality variables had a significant effect on customer purchasing decisions at PT. Ng Tech Supplies. Meanwhile, promotion has no effect on customer purchasing decisions at PT. Ng Tech Supplies.